HUBUNGAN POLA PEMBERIAN SUSU FORMULA DENGAN KEJADIAN EARLY CHILDHOOD CARIES (ECC) PADA ANAK PRASEKOLAH DI TK ISLAM DIPONEGORO KOTA SEMARANG - Erliana Jingga Lucitaningsih; Henry Setyawan; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Dental caries prevalence for children under 12 years in Indonesia in 2013 was 89% with a prevalence of children aged 3-5 years at 81.7%. Various causes of early childhood caries, one of which is the pattern of consumption of formula milk is not right. Giving formula milk or sweet liquid in a bottle that is too long attached to the surface of the tooth can cause dental caries in children. At previous research, it was found contradictory result. Thus, research on the association of formula milk feeding pattern with the incidence of Early Childhood Caries (ECC) was conducted. The purpose of this study was to analyze the relationship between the pattern of formula feeding with Early Childhood Caries (ECC) in preschool children in the Diponegoro Islamic Kindergarten in Semarang City. This type of research is an observational analytic study with a cross sectional approach. The population in this study were preschool children with a total of 188 children then the sample was taken as many as 66 children using the purposive sampling method. Data collection was done by interviewing and measuring dental caries. Data were analyzed using the Chi-Square test. 56 preschool children (84.8%) suffer from dental caries with 30 children having a def-t index in the very high category (score 6,6-14). Bivariate analysis using the Chi-Square test, shows the duration of milk consumption (p= 0.006; POR= 7.7), frequency of consumption (p= 0.017; POR= 9.6), duration of consumption (p= 0.013; POR= 11.1 ), night consumption only (p= 0.001; POR = 0.02), time for consuming milk in the morning, afternoon and night (p= 0,000; POR= 33), adding sugar (p= 0.016; POR= 12) is a risk factor Early Childhood Caries (ECC), and morning consumption only (p= 0.145), lunch consumption time only (p= 0.388), consumption time in the morning and evening (p= 1,000), time of consumption day and night (p= -) and bottle / pacifier use with the incidence of dental caries in preschool children is not proven to be a risk factor for Early Childhood Caries (ECC). Duration of consumption, frequency, duration, time, and addition of sugar in the consumption of formula milk are risk factors for Early Childhood Caries (ECC) in preschool children.